Sosialisasi Motivasi dan Organisasi bagi Anggota Mapala Surya Rimba, Universitas Muhammadiyah Purworejo - Hubi Rahmat Andika (Lembaga Pengembangan Kinerja Dosen, 2025)
Character development and organizational skills for students are essential aspects of the development of student organizations, including outdoor enthusiast groups. This activity aims to provide socialization on motivation, leadership, and organizational management to prospective members of MAPALA Surya Rimba at Muhammadiyah University of Purworejo. The community service activity was conducted on November 15, 2025, at 07:30 WIB, at the campus of Muhammadiyah University of Purworejo. This event is part of the 27th basic training (Diklatsar) series of MAPALA Surya Rimba. The methods used in this activity include interactive lectures, discussions, case studies, and organizational simulations. The results of the activity showed an increase in participants' understanding of achievement motivation, organizational management, roles of members, and basic coordination skills within an organization. Additionally, this activity triggered participants' awareness to build character, discipline, responsibility, teamwork, and to reflect the professional attitude of MAPALA members. This activity has the potential to be developed into a continuous development program to strengthen leadership quality and organizational management within MAPALA Surya Rimba.